Work Engagement Dominates Productivity in Indonesian Electricity Utility Employees - Khumaira, Made Ayu Alivy; Ikaningtyas, Maharani (Academia Open, 2026)
General Background: Employee productivity remains a fundamental determinant of organizational performance, particularly in public utility organizations operating in increasingly dynamic work environments. Specific Background: Maintaining high work productivity requires organizations to balance employees’ personal and professional responsibilities while cultivating organizational values and strengthening employee engagement. At PT PLN (Persero) UP3 Surabaya Utara, variations in productivity, uneven workloads, and delays in task completion indicate the need to examine organizational and individual factors associated with employee productivity. Knowledge Gap: Previous studies have separately examined work-life balance, organizational work culture, and work engagement, whereas empirical evidence integrating these variables within Indonesian electricity utility services remains limited. Aims: This study analyzes the relationships of Work-Life Balance, AKHLAK Work Culture, and Work Engagement with employee work productivity. Results: Using a quantitative approach with multiple linear regression on data collected from 76 employees, the findings demonstrate that all three variables simultaneously and partially show positive and significant relationships with work productivity. The coefficient of determination (R² = 0.822) indicates that the proposed model explains 82.2% of the variation in employee productivity, with Work Engagement representing the strongest contributor among the examined variables. Novelty: This study integrates Work-Life Balance, AKHLAK Work Culture, and Work Engagement into a single empirical model within the Indonesian electricity utility sector while identifying the dominant contribution of Work Engagement. Implications: The findings provide practical guidance for utility organizations to strengthen employee engagement alongside organizational culture and work-life balance initiatives to sustain higher levels of workforce productivity. Highlights: Employee involvement contributed the largest coefficient within the productivity model. Organizational values and personal balance consistently supported workforce performance. The proposed regression model accounted for most observed productivity variation Keywords: Work-Life Balance, AKHLAK Work Culture, Work Engagement, Employee Work Productivity, Human Resource Management